Cetuximab associated dermal filler reaction - Pathmanathan, Shivanshan (BMJ Case Rep, 2019)
A 52-year-old male patient with hyaluronic acid-based dermal fillers injected in his cheeks was diagnosed with glossotonsillary malignancy, and managed with concurrent cetuximab (epidermal growth factor receptor inhibitor) and radiation therapy. He developed significant inflammation around the dermal filler sites after first cycle of cetuximab which improved with dissolution of the dermal fillers with hyaluronidase. This suggests that cetuximab can lead to inflammation around the dermal filler sites, which can be treated with dissolution of the filler.